2012
DOI: 10.1631/jzus.b1100357
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents

Abstract: Abstract:In this paper, we described the symptoms and treatment of a patient with diabetic nephropathy accompanied by spontaneous retroperitoneal hemorrhage after hemodialysis. An elderly female patient with diabetic nephropathy presented with severe pain, numbness, and an increasing swelling in the left hip and left thigh after six sessions of hemodialysis involving the use of an antiplatelet drug and an anticoagulant agent. Her hemoglobin decreased to 46 g/L. An abdominal ultrasound showed a hematoma in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Although LMWH is an excellent alternative to unfractionated heparin because of its higher efficacy and safety, unfortunately, LMWH therapy is not without risks of spontaneous bleeding, such as in the abdominal wall, thigh and retroperitoneum, and the spinal and epidermal hematomas. [13][14][15][16][17][18] It was also noted that there is a relatively high bleeding risk with use of LMWH in some patients, such as in elderly patients with vascular diseases and in patients with renal insufficiency, diabetes, hypertension, or antineutrophil cytoplasmic antibody-related vasculitis. 19 In addition, renal impairment may lead to over-dosage, and/or an accumulative effect of LMWH may further cause bleeding complications in ESRD patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although LMWH is an excellent alternative to unfractionated heparin because of its higher efficacy and safety, unfortunately, LMWH therapy is not without risks of spontaneous bleeding, such as in the abdominal wall, thigh and retroperitoneum, and the spinal and epidermal hematomas. [13][14][15][16][17][18] It was also noted that there is a relatively high bleeding risk with use of LMWH in some patients, such as in elderly patients with vascular diseases and in patients with renal insufficiency, diabetes, hypertension, or antineutrophil cytoplasmic antibody-related vasculitis. 19 In addition, renal impairment may lead to over-dosage, and/or an accumulative effect of LMWH may further cause bleeding complications in ESRD patients.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, renal impairment may lead to over-dosage, and/or an accumulative effect of LMWH may further cause bleeding complications in ESRD patients. 13,20 Certainly, spontaneous renal hemorrhage in patients with diabetes receiving HD has been described. 21 A recent study by Wang et al indicated a 1.57-fold higher incidence of subdural hematoma in a cohort of 28,045 diabetic patients compared with 56,090 subjects without diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Massive retroperitoneal hematoma mostly results from rupture due to an abdominal aortic aneurysm or malignancy of retroperitoneal organs, most often the kidneys and adrenal glands . Spontaneous lumbar artery rupture is rare, and its incidence is still unknown.…”
Section: Introductionmentioning
confidence: 99%